EVALUATION OF ANTIHYPERGLYCEMIC ACTIVITY OF THE ALCOHOLIC EXTRACTS OF MOMORDICA CHARANTIA, TRIGONELLA FOENUM AND THEIR COMBINATIONS IN ANIMALS - VEERESH KUMAR.P; MANGILAL.T; R.NAGESWARA RAO (International Journal of Pharma and Bio Sciences, 2015)
Diabetes is one of the most common non-communicable diseases and a serious lifelong condition appearing worldwide. The study is aimed to demonstrate the antihyperglycemic activity of the alcoholic extracts of Momordica charantia, Trigonella foenum, and their combinations were used alloxan induced diabetic model in rats. The powdered Leaves of Trigonella foenum and Momardica Charantia were successively extracted in 100-150ml each of alcohol by using a Soxhlet extractor.The rats after alloxanization were given 5% w/v glucose solution in feeding bottles for the next 24 hours in their cages to prevent hypoglycemia. After 72 hours, rats with fasting blood glucose levels greater than 200 mg/dl were selected and used for the study. The blood samples were collected by retro orbital puncture at 0,1,2,4 and 8 hours after the administration. The treatment was continued for next 22 days.The blood glucose level was estimated at various time intervals by subjecting the collected blood to cold centrifugation for serum separation. Serum obtained was used for estimating the glucose level using GOD/POD (span) kit. The difference observed between the initial and final fasting blood glucose levels of extract treated hyperglycemic rats revealed the antihyperglycemic effect of Momordica Charantia, Trigonella foenum and their combinations throughout the period of study. The effect of three different extracts and their combinations are compared to that of reference standards, glibenclamide was found to be significant. In conclusion, these extracts showed significant anti-diabetic effect in diabetic rats after oral administration.